Epidemiology, clinical presentation and respiratory sequelae of adenovirus pneumonia in children in Kuala Lumpur, Malaysia - Lim, Li Min; Woo, Yen Yen; De Bruyne, Jessie Anne; Nathan, Anna Marie; Kee, Sze Ying; Chan, Yoke Fun; Chiam, Chun Wei; Eg, Kah Peng; Thavagnanam, Surendran; Sam, I-Ching (Public Library of Science, 2018)
Objectives To describe the severity, human adenovirus (HAdV) type and respiratory morbidity following adenovirus pneumonia in children. Methodology Retrospective review of children under 12 years of age, admitted with HAdV pneumonia, between January 2011 and July 2013, in a single centre in Malaysia. HAdV isolated from nasopharyngeal secretions were typed by sequencing hypervariable regions 1–6 of the hexon gene. Patients were reviewed for respiratory complications. Results HAdV was detected in 131 children of whom 92 fulfilled inclusion criteria. Median (range) age was 1.1 (0.1–8.0) years with 80% under 2 years. Twenty percent had severe disease with a case-fatality rate of 5.4%. Duration of admission (p = 0.02) was independently associated with severe illness. Twenty-two percent developed respiratory complications, the commonest being bronchiolitis obliterans (15.2%) and recurrent wheeze (5.4%). The predominant type shifted from HAdV1 and HAdV3 in 2011 to HAdV7 in 2013. The commonest types identified were types 7 (54.4%), 1(17.7%) and 3 (12.6%). Four out of the five patients who died were positive for HAdV7. Infection with type 7 (OR 8.90, 95% CI 1.32, 59.89), family history of asthma (OR 14.80, 95% CI 2.12–103.21) and need for invasive or non-invasive ventilation (OR 151.84, 95% CI 9.93–2.32E) were independent predictors of respiratory complications. Conclusions One in five children admitted with HAdV pneumonia had severe disease and 22% developed respiratory complications. Type 7 was commonly isolated in children with severe disease. Family history of asthma need for invasive or non-invasive ventilation and HAdV 7 were independent predictors of respiratory complications.